A facile and novel construction of attapulgite/Cu2O/Cu/g-C3N4 with enhanced photocatalytic activity for antibiotic degradation. Issue 3 (15th February 2017) - Zuo, Shixiang; Chen, Yao; Liu, Wenjie; Yao, Chao; Li, Xiazhang; Li, Zhongyu; Ni, Chaoying; Liu, Xiaoheng
Abstract: A high-performance photocatalyst, attapulgite/Cu2 O/Cu/g-C3 N4 (ATP/Cu2 O/Cu/g-C3 N4 ), was constructed via a one-pot redox strategy under anoxic calcination. The as-prepared composites were characterized by Fourier transform infrared spectra (FT-IR), X-ray diffraction (XRD), transmission electron microscopy (TEM), N2 adsorption-desorption isotherms (BET), photoluminescence emission (PL), and electrochemical impedance spectra (EIS). Results indicate that ultra-fine CuO nanoparticles on the surface of rod-like attapulgite are in-situ reduced by NH3 gas to generate Cu and minority Cu2 O during the pyrocondensation of melamine. Meanwhile, the generated g-C3 N4 membrane is uniformly encapsulated on the surface of attapulgite/Cu2 O/Cu to assemble Z-scheme Cu2 O/Cu/g-C3 N4 heterostructure. ATP/Cu2 O/Cu/g-C3 N4 shows improved visible light response ability and hole-electron suppression compared with ATP/g-C3 N4 . The photocatalytic performance and mechanism of the obtained photocatalyst for antibiotic degradation were evaluated by UV–Vis spectrometer and liquid chromatograph. ATP/Cu2 O/Cu/g-C3 N4 can exhibit favorable photocatalytic activity and reusability for chloramphenicol. In addition, h + and·OH radicals are the main active sites in the photocatalytic process, and Cu species play a vital role in separation and retarding recombination of electron-hole pairs.